Impaired autonomic function in adolescents born preterm. Issue 6 (29th March 2018) - Haraldsdottir, Kristin; Watson, Andrew M.; Goss, Kara N.; Beshish, Arij G.; Pegelow, David F.; Palta, Mari; Tetri, Laura H.; Barton, Gregory P.; Brix, Melissa D.; Centanni, Ryan M.; Eldridge, Marlowe W.
Abstract: Preterm birth temporarily disrupts autonomic nervous system (ANS) development, and the long‐term impacts of disrupted fetal development are unclear in children. Abnormal cardiac ANS function is associated with worse health outcomes, and has been identified as a risk factor for cardiovascular disease. We used heart rate variability (HRV) in the time domain (standard deviation of RR intervals, SDRR; and root means squared of successive differences, RMSSD) and frequency domain (high frequency, HF; and low frequency, LF) at rest, as well as heart rate recovery (HRR) following maximal exercise, to assess autonomic function in adolescent children born preterm. Adolescents born preterm (less than 36 weeks gestation at birth) in 2003 and 2004 and healthy age‐matched full‐term controls participated. Wilcoxon Rank Sum tests were used to compare variables between control and preterm groups. Twenty‐one adolescents born preterm and 20 term‐born controls enrolled in the study. Preterm‐born subjects had lower time‐domain HRV, including SDRR (69.1 ± 33.8 vs. 110.1 ± 33.0 msec, respectively, P = 0.008) and RMSSD (58.8 ± 38.2 vs. 101.5 ± 36.2 msec, respectively, P = 0.012), with higher LF variability in preterm subjects. HRR after maximal exercise was slower in preterm‐born subjects at 1 min (30 ± 12 vs. 39 ± 9 bpm, respectively, P = 0.013) and 2 min (52 ± 10 vs. 60 ± 10 bpm, respectively, P = 0.016). This study is the first report of autonomic dysfunction in adolescents born premature. Given prior association of impaired HRV with adult cardiovascular disease, additional investigations into the mechanisms of autonomic dysfunction in this population are warranted. Abstract : Preterm birth interrupts the third trimester of gestation, resulting in altered development of several key physiological systems, including the autonomic nervous system, though the long‐term implications in adolescent children are not completely understood. Otherwise healthy adolescent children underwent resting heart rate variability monitoring and maximal exercise testing, and were found to have significantly slower heart rate recovery following maximal exercise and altered resting heart rate variability, suggesting autonomic dysfunction. Cardiovascular disease risk is high in individuals with autonomic dysfunction, suggesting a need for further investigation into autonomic function in this population.